District-Wide Effects on Data Use in the Classroom - Wayman, Jeffrey C.; Cho, Vincent; Jimerson, Jo Beth; Spikes, Daniel D. (Education Policy Analysis Archives, 2012)
In the present study, an examination is conducted in three school districts of how data are used to improve classroom practice.  In doing so, we explore the effects that attitudes toward data, principal leadership, and computer data systems have on how data are used to affect classroom practice.  Findings indicate that educators are ambivalent about data: they see how data could support classroom practice, but their data use operates in the presence of numerous barriers.  Many of these barriers are due to principal leadership and computer data systems; these barriers often have negative effects on attitudes toward data and disrupt the progression from using data to inform classroom practice.  It is hypothesized that many of these barriers can be removed through effective district policies to improve structures and supports for using data.